Assessment of human impact on the environment Karachaganak fi eld (Journal of Geography and Environmental Management, 2016)
This article assesses the impact on the environment of the Karachaganak fi eld, based on the methodology of «Modern theory and practice of assessing the impact of activities on the environment».